Analysing decentralised natural resource governance: proposition for a "politicised? institutional analysis and development framework - Clement, Floriane (Springer, 2010)
There has often been a gap between policy intentions and outcomes in the field of natural resource governance. Analysing the factors for these discrepancies requires multi-level approaches that relate policy decisions formulated at the national and international level with the decisions of local resource users. A key asset of the Institutional Analysis and Development framework is precisely its ability to link multiple governance levels. Yet most commons literature has been limited to the study of collective action among local communities without considering higher institutional and government levels. To overcome this limitation, I posit for a methodological development of the framework, which bridges the gap between institutional analysis, power-centred and historical approaches, and discourse analysis. The application of the extended framework to the study of state afforestation policies in Vietnam highlights the need to simultaneously consider institutions, the politico-economic context and discourses across governance and government levels. As illustrated in this paper, such a framework does not only facilitate the analysis of policy shortcomings but also supports the design and dissemination of policy recommendations.